INFORMATION TECHNOLOGY GOVERNANCE ANALYSIS USING COBIT 5 FRAMEWORK AT SMPN 18 BANDAR LAMPUNG - Salsabila Indriyani; Priandika, Adhie Thyo (Informatika, Universitas Jenderal Soedirman, 2024)
So far, the management of Information Technology at SMPN 18 Bandar Lampung has not held an information technology governance analysis, so that the application of information technology infrastructure cannot be known at the maturity level. This study aims to determine the level of maturity of the application of information technology required information technology governance analysis. The method used in the COBIT 5 framework is up to phase 4 - Plan Programe, the calculation used is by finding the statistical average or mean value in the form of the total value of the various items contained in the questionnaire. The results of this research the average maturity index value is 3.4 and (maturity level as is) in the APO, BAI, and MEA domains, at level 3 in the APO, BAI, MEA domains. Based on the results of the research, the researcher provides suggestions regarding the procedures chosen based on the research findings to help the information technology infrastructure of SMPN 18 Bandar Lampung reach the required maturity level.